1977
DOI: 10.6028/nbs.ir.77-1313
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the technical literature on emergency egress from buildings

Abstract: The NBS-OSHA Emergency Escape Requirements Project is directed at identifying the data base, assessing the capabilities of selected elements, and providing the technical basis of hazard assessment as each relates to emergency escape from the workplace. The HEW-NBS Life/Fire Safety Program involves a series of interrelated projects in the areas of decision analysis, fire and smoke detection, smoke movement and control, automatic extinguishment, and the behavior of institutionalized populations in fire situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…For various generalizations of the approach we shall consider, see Chalmet,Francis and Saunders [2], and Francis and Saunders [4]. For a general discussion of the evacuation literature, see Stahl and Archea [7].…”
Section: Introductionmentioning
confidence: 99%
“…For various generalizations of the approach we shall consider, see Chalmet,Francis and Saunders [2], and Francis and Saunders [4]. For a general discussion of the evacuation literature, see Stahl and Archea [7].…”
Section: Introductionmentioning
confidence: 99%
“…(25), (26), (27). The minimum evacuation time via the staircase is ( 9 ) t 10 h G + 15 h G n (0) MUller suggested the limitation of building height rather than to widen the staircases.…”
Section: Flow Models Based On the Carrying Capacity Of Independent Egmentioning
confidence: 99%
“…Theoretical conceptualizations have begun to emerge suggesting the existence of some relationship between "cognitive sets" held by individual occupants, environmental and social context, and actions actually taken during a fire situation (Breaux et.al., 1976;Stahl, 1977;Bickman, 1977). By cognitive set I mean the complex network of attitudes and prior experiences through which humans are predisposed to interpret, organize, and respond to current events.…”
Section: Issuesmentioning
confidence: 99%
“…This notion is widely accepted, and research interest in human behavior in fires has increased during the 1970's. Several reviews document this development (e.g., Rubin andCohen, 1974, Pauls, 1975;Breaux et.al., 1976;Stahl and Archea, 1977). Reviews of the literature on occupant response to fires have identified three categories of research effort: the development of explanatory models (e.g., Archea, 1977;Bickman, 1977;Stahl, 1976Stahl, , 1977; the development of specific techniques for gathering data (e.g., Pauls, 1975Pauls, , 1977; and the description of actual fire events (e.g., Wood, 1972;Bickman, 1976;Haber, 1977;Bryan, 1977;Lerup, 1977).…”
mentioning
confidence: 99%